99Mo and 67Cu isotope yields under production conditions of NSC KIPT electron accelerator KUT-30 - Aizatsky, N.I.; Diky, N.P.; Dovbnya, A.N.; Ehst, D.; Lyashko, Yu.V.; Nikiforov, V.I.; Tenishev, A.Eh.; Torgovkin, A.V.; Uvarov, V.L.; Shevchenko, V.A.; Shramenko, B.I. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
Computer simulation has been used to determine the 99Mo and 67Cu isotope yields, as well as the radiation power absorbed in technological natural Mo- and Zn-based targets of different mass and geometry, and also, the power absorbed in a tantalum converter versus the converter thickness and spatial-energy characteristics of the electron beam from the accelerator KUT-30 (energy up to 45 MeV, average beam current up to 300 μA). The results of experimental studies are in good agreement with the simulation data. Методом компьютерного моделирования определены выход изотопов 99Мо, 67Сu и поглощенная мощность излучения в технологических мишенях различной массы и геометрии на основе природных Мо и Zn, а также поглощенная мощность в конвертере из тантала в зависимости от толщины конвертера и пространственно-энергетических характеристик пучка электронов ускорителя КУТ-30 (энергия – до 45 МэВ, средний ток – до 300 мкА). Результаты экспериментального исследования находятся в удовлетворительном соответствии с данными моделирования. Методом комп'ютерного моделювання визначено вихід ізотопів 99Мо, 67Сu і поглинута потужність випромінення в технологічних мішенях різної маси і геометрії на основі природних Мо і Zn, а також поглинута потужність у конвертері з танталу в залежності від товщини конвертера і просторово-енергетичних характеристик пучка електронів прискорювача КУТ-30 (енергія – до 45 МеВ, середній струм – до 300 мкА). Результати експериментального дослідження знаходяться в задовільній відповідності з даними моделювання.